Effect of electroacupuncture on metabolic level and quality of life in patients with obese polycystic ovary syndrome: a randomized controlled trial - Wang, Yuqing; Fu, Liying; Wang, Jiqing; Fang, Xiaoqin; Xu, Shifen; Li, Shanshan; Mi, Yiqun (Frontiers in Endocrinology, 2026)
ObjectiveThis study aims to investigate the effects of electroacupuncture (EA) intervention on patients with obese polycystic ovary syndrome (PCOS), with specific analysis focusing on the following dimensions: 1) whether EA can reduce patients’ body mass index (BMI); 2) to evaluate the regulatory effect of EA on key endocrine and metabolic indicators of patients, including blood glucose, blood lipids, and sex hormones; 3) to examine whether EA can improve reproduction-related outcomes in patients, such as abnormal menstrual cycles, abnormal menstrual flow, abnormal endometrial thickness, and ovulatory dysfunction; and 4) to verify the effect of EA in improving patients’ quality of life. Furthermore, this study intends to provide evidence-based support for the optimization of clinical non-pharmacological intervention strategies for obese PCOS.MethodsThis was a patient- and assessor-blinded, randomized, sham-controlled trial, enrolling 106 female patients with obese PCOS aged 18–45 years. Participants were randomly assigned to two groups: the EA group and the sham EA group. The treatment duration was 12 weeks, with a 12-week follow-up period after treatment completion. The intervention frequency was adjusted in stages: three sessions/week during Weeks 1–4, two sessions/week during Weeks 5–8, and one session/week during Weeks 9–12, resulting in a total of 24 treatment sessions throughout the entire course. The primary outcome was the change in BMI from baseline to the end of the 12-week intervention. Secondary outcomes included changes in body composition, glucose metabolism indicators, lipid metabolism parameters, sex hormone levels, endometrial thickness, ovarian volume, menstrual cycle, and scores on the validated Chinese version of the Polycystic Ovary Syndrome Health-Related Quality of Life Questionnaire (PCOSQ).ResultsAmong the 106 patients (mean (SD) age, 27.93 (3.47) years) included in the intention-to-treat analysis, 104 (98%) completed all outcome measurements at week 24, and 2 (2%) dropped out of the trial. The mean difference in BMI from baseline to week 12 within the EA group was −2.46 (95%CI, −2.67 to −2.18). At week 12, the difference in BMI score was -1.50 (95%CI, -1.83 to -1.17;P<.001) between the EA and SA groups. The efficacy of EA was sustained during the 24-week post-intervention follow-up (mean difference, -1.58;95% CI: -2.05 to -1.10; P<.001). Significant improvements were also observed in the waist-hip ratio (WHR) and body fat mass (BFM). The mean difference in WHR and BFM from baseline to week 12 within the EA group were -0.04 (95%CI, −0.06 to −0.04) and -4.56 (95%CI, −5.10 to −4.02). At week 12, the difference in WHR score was -0.03 (95%CI, -0.04 to -0.01;P<.001) between the EA and SA groups, in BFM was -2.92 (95%CI, -3.52 to -2.33;P<.001). For sex hormones, the mean difference in prolactin (PRL) and estradiol (E2) from baseline to week 12 within the EA group were -109.10 (95%CI, -154.60, -62.63) and 12.99 (95%CI, -17.45, 43.43), respectively. Regarding glucose metabolism, the mean difference in fasting glucose (FPG), fasting insulin (FINS), and calculated insulin resistance (HOMA-IR) from baseline to week 12 within the EA group were -0.30 (95%CI, -0.41, -0.18), -46.03(95%CI, -61.27, -30.79), and -12.70 (95%CI, -18.58, -6.81), respectively. For lipid profiles, the mean difference in total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-C) from baseline to week 12 within the EA group were -0.30 (95%CI, -0.40, -0.20), -0.44 (95%CI, -0.64,-0.25), and -0.30 (95%CI, -0.43, -0.16), respectively. PCOSQ improvements from baseline consistently favored EA at all timepoints. No serious adverse events were reported. No serious adverse events were reported.ConclusionElectroacupuncture is an effective intervention for managing weight, improving metabolism and enhancing the quality of life in patients with obese PCOS. The benefits of BMI and PCOSQ last for at least 24 weeks.Clinical Trial Registrationhttps://www.chictr.org.cn, identifier ChiCTR2300070722.